CURRENT TENDENCIES OF THE GLOBAL INDUSTRIAL POLICY AND RUSSIAN INDUSTRIAL RESTRUCTURING PRIORITIES - A. A. Chernyshev (Vestnik MGIMO-Universiteta)
This article is devoted to the analysis of restructuring in the Russian production sector basing on the worldwide experience of innovative industrial policy with the focus on the role of the government in this process. While the author in the article identifies de- and re-industrialization trends, cluster systems organization as well as development of national innovation systems (NIS) as crucial processes in the global industry great attention is paid to the role of the state in these processes. International practice in developed countries shows that the state plays key role in industrialization process acting as a brainchild in setting target values for R&D industrial expansion implementing institutional, infrastructure, preferential as well as tax relief forms of support. Major advanced economies devote considerable attention to creation of supportive environment for industrial development, including implementation of national innovation systems (NIS) as well as elaboration of the institutional infrastructure industry development programs. Global market industrial trends analysis shows that production sector together with its innovative development will remain a major priority and a driving force in global economic growth. Taking into account present situation of the Russian economy which can be described as critical, time factor is considered to be of great importance, making it necessary to adopt accelerated development model in the Russian economy reforms. A key question to consider is what actions should be adopted by the government to ensure acceleration in economic development of the country.